HUBUNGAN TROMBOSITOPENIA, HIPOALBUMINEMIA, DAN SPLENOMEGALI SEBAGAI PREDIKTOR VARISES ESOFAGUS PADA PASIEN SIROSIS HATI DI RSUD DR. SOEDARSO PONTIANAK - ., Yenni Andriana (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Liver cirrhocis is a disease that most found in the worldincluded Indonesia, with the major bleeding complication that esophagealvarices broken which has high mortality rate. Thus, it needs a predictor topredict the occurrence of esophageal varices, they are simply the numberof trombocyt, albumin levels, and splenomegaly, in Dr. Soedarso generalhospital Pontianak has never implemented.Methodology: This research is an obvervational analytic research andcross sectional's approach. The data was collected in the medical recordsof Dr. Soedarso general hospital Pontianak on the 1-8 January, 2011.Thedata was collected from 96 samples using medical record. The data wasanalyzed using Chi-square test.Result: There are 47 people (49%) the research's subject havetrombocytopenia, 67 people (69%) have hypoalbuminemia, and 29 people(31%) have splenomegaly. There is a significant relationship oftrombocytopenia (p = 0,000), hypoalbuminemia (p = 0,001), splenomegaly(p = 0,000), with esophageal varices. The strength measurementrelationship of varices esophagus from the biggest to the smallest arehypoalbuminemia (p = 0,241), trombocytopenia (p = 0,227), andsplenomegaly (p = 0,008). According to the ROC Curve, this comparisonhas value of 92%, is very strong.Conclusion: There is a relationship between trombocytopenia,hypoalbuminemia, splenomegaly, and varises esofagus to cirrhoticpatients in Dr. Soedarso general hospital Pontianak in the year 20092010.Trombocytopenia, hypoalbuminemia and splenomegaly can bepredicts varices esophageal.